KONFLIK KERJA, STRES KERJA, KECERDASAN EMOSIONAL DAN KINERJA PEGAWAI DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA DENPASAR - IGA Wirati Adriati; Ni Luh Leoziana Agustin (Universitas Pendidikan Nasional, 2017)
Work Conflict, Work Stress, Emotional Intelligence and Staff Performance at Public Works and Spatial Planning Agency Denpasar. Government agencies serving in community service must have good employee performance. This study aimed to analyze the effect of work conflicts, work stress, emotional intelligence, and employee performance in the department of public works and spatial planning of Denpasar city. The technique of collecting samples in this study was simple random sampling with total 40 respondents. The research method used is the method of quantitative data with the help of SPSS 20.00. Data analysis were included validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation analysis, coefficient of determination (R2), t test and F test. The result of multiple correlation analysis R = 0.705, simultaneously showed that there was strong positive relationship between the independent variables to the dependent variable. The result of coefficient of determination (R2) was equal to 0,455 that 45,5% independent variable influence to dependent variable in the department of public works and spatial planning of Denpasar city, while the rest equal to 54,5% were caused by other variables which were not included in this research. The result of t test, conflict variable of regression coefficient coefficient obtained value equal to -0,315 and significance value 0,047 show work conflict variable have significant negative effect to employee performance. Work stress obtained value of -0.450 and a significance value of 0.007 showing work stress variable had a significant negative effect on employee performance. Emotional intelligence variable obtained value of 0.600 and a significance value of 0,000 which showed the emotional intelligence variable had a significant positive effect on employee performance. The calculation results obtained the value of F count work conflict variable (X1), work stress (X2), emotional intelligence (X3) had a positive effect simultaneously on the performance of employees in the Public Works Department and Spatial Planning Denpasar. Keywords: work conflicts, work stress, emotional intelligence, employee performance